Obtenção e caracterização química do óleo essencial da parte aérea do “cipó-mil-homens” (Aristolochia triangularis Cham.): resgate de planta nativa da América do Sul - Sartor, Julia Faversani (2024)
Aristolochia triangularis Cham., popularly known as <cipó-mil-homens=, is a native plant to South America and it is normally found in the Atlantic forest. The plants of the botanical genus, Aristolochia, are used in traditional medicine for their medicinal properties. The A. triangularis has antibacterial, antimycobacterial and antifungal action, being commonly used in the southwest of Paraná as tea, in the treatment of stomach ails. This work aimed at the rescue of Aristolochia triangularis Cham. through the characterization of the essential oil obtained from the vine. The material was collected in the urban area of Pato Branco city, and the material went through three different drying times (120, 7 and 18 days). The essential oil’s acquisition was performed using the hydrodistillation method by the Clevenger apparatus. The samples of essential oil were analyzed and identified by gas chromatography coupled to mass spectrometry (GC/MS), and by calculating the arithmetic index (AI) obtained from the co-injection of n-alkane standards and by comparison with the mass spectra. The obtained yield in the three hydrodistillations were: 0,210%; 0,240% and 0,400%. In terms of yield and less hydrodistillation time, the essential oil of the third hydrodistillation is chosen (with 18 days of drying and 2 hours of extraction). In relation to the chemical composition of the essential oil of A. triangularis Cham., the major components identified were (E)-methyl isoeugenol, -eudesmol and alloaromadendrene epoxide in all essential oil samples. Furthermore, the essential oil of the first hydrodistillation obtained a bigger number of identified compounds (27 compounds) in comparison to the second and the third hydrodistillations (both with 19 compounds). Therefore, if the objective is the identification of secondary metabolites in the essential oil, then the best option would be the first hydrodistillation (with 120 days of drying and 2,5 hours of extraction). Thus, the obtained results were relevant to the study of the A. triangularis Cham. essential oil, enabling to establish the best drying time and also the best extraction time in accordance with the final goal in relation to the yield or chemical composition.